Analysis of Spatiotemporal Changes and Driving Forces of Vegetation Coverage in Foshan City, Guangdong Province - Yang, Yongzhong; Wang, Ruei-Yuan (International Journal of Environment, Agriculture and Biotechnology, 2024)
Quantitative analysis of the spatiotemporal distribution characteristics and driving forces of regional fractional vegetation coverage (FVC) is of great significance for promoting urban ecological protection and high-quality development. This study utilized the GEE platform and Landsat series remote sensing data to invert the FVC of Foshan City from 2001 to 2020 based on a pixel binary model. The spatial pattern and spatiotemporal variation characteristics were analyzed, and combined with meteorological, topographic, and land use data of the same period in the region, Sen +Mann Kendall trend analysis and parameter optimal geographic detector model were used to analyze its driving factors. The results showed that: 1. From 2001 to 2020, the overall vegetation coverage showed a slight downward trend (with a reduction rate of 2.87%), and the average vegetation coverage over the years was 51.53%, indicating that the vegetation coverage in the study area was generally at a moderate level. In terms of spatial distribution, the overall vegetation coverage shows a pattern of "high in the northwest and low in the southeast," with significant regional differences, and the types are mainly moderate and low vegetation coverage. 2. The proportion of vegetation improvement areas in the research area is 49.53%, which is larger than the area of degraded areas. 3. In the detection of driving factors, land use type is the main driving factor with an average explanatory power of 61.25%, while vegetation, topography, precipitation, and altitude are secondary driving factors; The explanatory power (Q value) of the interaction between each factor is higher than that of a single factor, showing a synergistic and nonlinear enhancement relationship between two factors.